Dynamical Modeling and Active Vibration Control Analysis of a Double-Layer Cylindrical Thin Shell with Active Actuators - Yu Wu; Rui Huo (Sci)
The application of double-layer shell structure is very common in some situations that require complex loads and vibrations, such as key components such as the shell and wings of aerospace engines, and the shell of underwater vehicles. Many authors have conducted research on the vibration and acoustic radiation characteristics of double-layer cylindrical shells. By adding reinforcement and ribs between the double-layer cylindrical shells and optimizing structural design, passive vibration control techniques can effectively solve high frequency vibration problems, but the impact on mid to low frequency vibrations is still limited. Therefore, this article conducts theoretical research on a novel active vibration control method that inserts an active actuator between a double-layer cylindrical shell to achieve better mid low frequency vibration control effects. Firstly, the substructure admittance method is applied to analytically and dynamically model a double-layer cylindrical thin shell structure with active support, and the vibration power flow of the system is theoretically derived to evaluate the vibration reduction effect. Then, numerical simulation analysis was conducted on the influence of different configurations of six feedback control parameters, time delays, and other factors on the vibration power flow. Finally, based on the image, the conclusion is drawn that all six feedback control parameters can improve the vibration control effect of the coupled system to a certain extent, but not every feedback control parameter has a prominent effect, and the effective range of some parameters is relatively narrow.